Lanthanum ion modified zeolite adsorbent as well as preparation method and application thereof

Through the preparation of lanthanum ion modified zeolite adsorbent, the problem of insufficient adsorption capacity of traditional modified zeolite materials on phosphate is solved, and high-efficiency phosphate adsorption and recycling of materials are achieved, which is suitable for eutrophication treatment of water bodies.

CN119588303AInactive Publication Date: 2025-03-11UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202510138166.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional modified zeolite materials lack adsorption capacity and stability on phosphate, and cannot be effectively recycled, making it difficult to solve the problem of phosphorus pollution caused by eutrophication of water bodies.

Method used

By mixing artificial zeolite particles with sodium salt solution, stirring, filtering, drying and calcining, a precursor was obtained, and then mixed with lanthanum salt solution, stirring, filtering, drying and calcining, a lanthanum ion modified zeolite adsorbent was prepared. This method uses lanthanum ion modification to improve the surfactivity and adsorption capacity of zeolite materials, and remove impurities through high-temperature calcination to improve the circulation performance of the materials.

Benefits of technology

It has achieved efficient phosphate adsorption of lanthanum ion modified zeolite adsorbent and fixed phosphorus in sediments. The material is cheap and easy to promote, and is suitable for eutrophication treatment and emergency treatment of water bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588303A_ABST
    Figure CN119588303A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorbents, and particularly relates to a lanthanum ion modified zeolite adsorbent as well as a preparation method and application thereof. Compared with the prior art, the method has the advantages that sodium ions are used for replacing aluminum ions which are originally large in size in the artificial zeolite to enable the salt-modified artificial zeolite material to have higher surface activity, then high-temperature calcination is used for removing impurities which are firmly combined with a pore channel structure in the artificial zeolite material, and the surface activity of the material is further improved; lanthanum in the lanthanum ion modified zeolite adsorbent exists in the form of lanthanum oxide after the lanthanum ion modified zeolite adsorbent is calcined, the surface of the lanthanum ion modified zeolite adsorbent is in an electron-deficient state and is expressed as Lewis acid, the lanthanum ion modified zeolite adsorbent is combined with water molecules to form hydrated oxide, and the hydrated oxide can generate electrostatic adsorption with phosphate ions to generate a complex; the method realizes efficient adsorption of phosphorus and fixation of phosphorus in sediments, so that the effect of removing phosphate radicals in the water body is achieved, the material cost is low, and the method has a good application prospect in the aspects of eutrophication treatment and emergency treatment of the water body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbents, and in particular relates to a lanthanum ion modified zeolite adsorbent, a preparation method and application thereof. Background Art

[0002] Global water security is essential to achieving sustainable development for mankind, and water pollution remains a challenge we must face. Among these challenges, eutrophication caused by high phosphorus content in water bodies is particularly critical. In severe cases, eutrophication of water bodies can cause hypoxia in water bodies, leading to outbreaks of cyanobacteria and mass death of aquatic organisms, affecting aquatic ecosystems and human health. In order to solve this problem, countries around the world have conducted extensive research. At present, common treatment methods include dredging, chemical adsorption, plant ecological restoration, and the "biological + ozone" process that has emerged in recent years. Among these common treatment methods, chemical adsorption treatment has become the most common method for the treatment of phosphorus pollution in water bodies because of its simple operation and fast effect.

[0003] Traditional chemical treatment methods have problems such as long process flow, large land occupation, large equipment investment, and large amount of chemical sludge. In recent years, with the development and application of rare earth resources, new adsorbents prepared based on modified clay materials have been widely used. Among them, zeolite materials have a unique pore structure, high stability and high adsorption efficiency in water, low price, strong adsorption capacity, and are widely used in the fields of water treatment adsorption and catalysis. However, the adsorption of phosphate by traditional modified zeolite materials is mainly physical adsorption, and they lack adsorption capacity and stability; and traditional modified zeolite materials mostly use natural zeolites, but natural zeolites have poor desorption effects after adsorption and cannot be recycled. Although the pore size and shape of artificial zeolites can be adjusted compared to natural zeolites, due to their compact structure, they are not easy to load other metal ions, and traditional mechanical stirring cannot form an effective load. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a lanthanum ion modified zeolite adsorbent with high adsorption capacity and good circulation performance, and a preparation method and application thereof.

[0005] The present invention provides a method for preparing a lanthanum ion modified zeolite adsorbent, comprising the following steps: S1) mixing artificial zeolite particles with a sodium salt solution, stirring, filtering, drying, and calcining to obtain a precursor; S2) mixing the precursor with a lanthanum salt solution, stirring, filtering, drying, and calcining to obtain a lanthanum ion-modified zeolite adsorbent.

[0006] Preferably, the sodium salt solution is selected from sodium chloride solution; the mass concentration of the sodium salt solution is 0.5% to 2%; The lanthanum salt solution is selected from lanthanum chloride solution; the mass concentration of the lanthanum salt solution is 0.4% to 1%.

[0007] Preferably, the mesh size of the artificial zeolite particles is 100-300 meshes.

[0008] Preferably, the artificial zeolite particles are prepared according to the following steps: The artificial zeolite is ball-milled and sieved to obtain artificial zeolite particles; the rotation speed of the ball mill is 200-11500 r / min; and the ball milling time is 1-8 h.

[0009] Preferably, the ratio of the artificial zeolite particles to the sodium salt solution is 0.02-0.1 g: 1 mL; The ratio of the precursor to the lanthanum salt solution is 0.05-0.1 g:1 mL.

[0010] Preferably, the mixing and stirring time in step S1) is 2 to 3 hours; The mixing and stirring time in step S2) is 1 to 3 hours.

[0011] Preferably, the calcination temperature in step S1) is 300°C to 500°C; the calcination time is 5 min to 1 h; In the step S2), the calcination temperature is 200° C. to 500° C., and the calcination time is 30 min to 2 h.

[0012] The present invention also provides a lanthanum ion modified zeolite adsorbent prepared by the above preparation method.

[0013] The present invention also provides a method for water treatment, comprising the following steps: The lanthanum ion modified zeolite adsorbent prepared by the above preparation method is used to adsorb phosphorus-containing water.

[0014] Preferably, the lanthanum ion-modified zeolite adsorbent after adsorption treatment is shaken in water to obtain a regenerated lanthanum ion-modified zeolite adsorbent; the regenerated lanthanum ion-modified zeolite adsorbent is used for adsorption treatment of phosphorus-containing water bodies.

[0015] The present invention provides a preparation method of a lanthanum ion modified zeolite adsorbent, comprising the following steps: S1) mixing artificial zeolite particles with a sodium salt solution, stirring, filtering, drying, and calcining to obtain a precursor; S2) mixing the precursor with a lanthanum salt solution, stirring, filtering, drying, and calcining to obtain a lanthanum ion modified zeolite adsorbent. Compared with the prior art, the present invention first uses sodium ions to replace the originally larger aluminum ions in the artificial zeolite so that the salt-modified artificial zeolite material has a higher surface activity, and then uses high-temperature calcination to remove impurities firmly bound to the pore structure in the artificial zeolite material, further improving the surface activity of the material, and then uses lanthanum ions to modify it. After calcination, lanthanum in the lanthanum ion modified zeolite adsorbent exists in the form of lanthanum oxide, and its surface is in an electron-deficient state, showing a Lewis acid, and combines with water molecules to form a hydrated oxide, which can produce electrostatic adsorption with phosphate ions to generate a complex, realize efficient adsorption of phosphorus and fixation of phosphorus in sediments, thereby achieving the effect of removing phosphate from water bodies, and the material cost is low, easy to promote, and has good application prospects in water eutrophication control and emergency disposal. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a comparison chart of the phosphorus adsorption performance of artificial zeolite, modified zeolite and lanthanum ion modified zeolite adsorbent in Example 1 of the present invention; Figure 2 This is a diagram showing the recycling results of the lanthanum ion-modified zeolite adsorbent obtained in Example 1 of the present invention; Figure 3 is an adsorption isotherm curve of the lanthanum ion modified zeolite adsorbent obtained in Example 1 of the present invention; Figure 4 This is a diagram showing the recycling results of the lanthanum ion-modified zeolite adsorbent obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] The present invention provides a preparation method of a lanthanum ion modified zeolite adsorbent, comprising the following steps: S1) mixing artificial zeolite particles with a sodium salt solution, stirring, filtering, drying and calcining to obtain a precursor; S2) mixing the precursor with a lanthanum salt solution, stirring, filtering, drying and calcining to obtain a lanthanum ion modified zeolite adsorbent.

[0019] The present invention firstly utilizes sodium ions to replace the aluminum ions originally having a large volume in the artificial zeolite so that the salt-modified artificial zeolite material has higher surface activity, then utilizes high-temperature calcination to remove impurities firmly bound to the pore structure in the artificial zeolite material, further improves the surface activity of the material, and then utilizes lanthanum ions to modify it. After calcination, the lanthanum in the lanthanum ion-modified zeolite adsorbent exists in the form of lanthanum oxide, and its surface is in an electron-deficient state, showing Lewis acid, and combines with water molecules to form a hydrated oxide, which can generate electrostatic adsorption with phosphate ions to generate a complex, realizes efficient adsorption of phosphorus and fixation of phosphorus in sediments, thereby achieving the effect of removing phosphate from water bodies, and the material cost is low, easy to promote, and has good application prospects in the treatment of eutrophication of water bodies and emergency disposal.

[0020] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.

[0021] According to the present invention, the mesh number of the artificial zeolite particles is preferably 100-300 mesh; optionally, the mesh number of the artificial zeolite particles is 100 mesh, 150 mesh, 200 mesh, 300 mesh or a range between any two of the above values; in the embodiment provided by the present invention, 150 mesh is specifically used as an example for description.

[0022] According to the present invention, the artificial zeolite particles are preferably prepared according to the following steps: the artificial zeolite is ball-milled and sieved to obtain the artificial zeolite particles; the ball milling is preferably dry ball milling; a ball milling aid is preferably added to the ball milling; the ball milling aid is preferably stearic acid; the mass of the ball milling aid is preferably 0.05% to 0.5% of the mass of the artificial zeolite, more preferably 0.1% to 0.3%, and more preferably 0.1%; the ball-to-material ratio of the ball milling is preferably 1: (0.5 to 2), more preferably 1: (0.8 to 1.2), and more preferably 1: 1; the rotation speed of the ball mill is preferably 200 to 11500 r / min, more preferably 500 to 11000 r / min, more preferably 1000 to 10000 r / min, more preferably 5000 to 10000 r / min, and most preferably 8000 r / min; the ball milling time is preferably 1 to 8 h, more preferably 1 to 5 h, and more preferably 1 to 3 h; the mesh number of the sieve used for screening is preferably 100-300 mesh; optionally, the mesh number of the sieve is 100 mesh, 150 mesh, 200 mesh, 300 mesh or a range between any two of the above values; in the embodiment provided in the present invention, 150 mesh is specifically used as an example for explanation.

[0023] The artificial zeolite particles are mixed and stirred with a sodium salt solution; the sodium salt solution is a sodium salt solution well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably a sodium chloride solution; the mass concentration of the sodium salt solution is preferably 0.5% to 2%; optionally, the mass concentration of the sodium salt solution is 0.5%, 0.8%, 1%, 1.5%, 2% or a range between any two of the above values; the ratio of the artificial zeolite particles to the sodium salt solution is preferably 0.02 to 0.1 g: 1 mL; optionally, the ratio of the artificial zeolite particles to the sodium salt solution is 0.02 g: 1 mL, 0.05 g: 1 mL, 0.08 g: 1 mL, 0.1 g: 1 mL or a range between any two of the above values; the mixing and stirring time is preferably 2 to 3 h. In the NaCl solution, due to the volume effect, after the sodium ions replace the aluminum ions that are originally larger in the artificial zeolite, the effective pore size of the artificial zeolite will become larger, the steric hindrance will become smaller, the internal diffusion rate will be accelerated, and the exchange capacity will increase. Therefore, the salt-modified artificial zeolite material has higher surface activity.

[0024] After mixing and stirring, filtering, drying and calcining are performed to obtain a precursor; the calcination temperature is preferably 300°C to 500°C; optionally, the calcination temperature is 300°C, 350°C, 400°C, 450°C, 500°C or a range between any two of the above values; the calcination time is preferably 5 min to 1 h; optionally, the calcination time is 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 1 h or a range between any two of the above values. High-temperature calcination can remove impurities firmly bound to the pore structure in the artificial zeolite material and further improve the surface activity of the material. Combining salt treatment with high-temperature calcination can transform the inner and outer surfaces of the material without destroying the lattice framework of the raw material. Improve the ion exchange performance of the material.

[0025] The precursor is mixed and stirred with a lanthanum salt solution; the lanthanum salt solution can be a lanthanum salt solution well known to those skilled in the art, without any special restrictions, and is preferably a lanthanum chloride solution in the present invention; the mass concentration of the lanthanum salt solution is preferably 0.4% to 1%; optionally, the mass concentration of the lanthanum salt solution is 0.4%, 0.6%, 0.8%, 1% or a range between any two of the above values; the mixing and stirring time is preferably 1 to 3 h; optionally, the mixing and stirring time is 1 h, 1.5 h, 2 h, 2.5 h, 3 h or a range between any two of the above values.

[0026] After mixing and stirring, filtering, drying and calcining are performed to obtain a lanthanum ion modified zeolite adsorbent; the calcination temperature is preferably 200°C to 500°C; optionally, the calcination temperature is 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C or a range between any two of the above values; the calcination time is preferably 30 min to 2 h; optionally, the calcination time is 30 min, 40 min, 50 min, 60 min, 1 h, 1.5 h, 2 h or a range between any two of the above values. Salt thermal modification does not significantly improve the adsorption performance, because the silicon oxygen structure of artificial zeolite itself is negatively charged and has no adsorption capacity for phosphate ions with the same negative charge; after salt thermal modification, the pore size of artificial zeolite becomes larger and the ion exchange capacity becomes stronger, but the crystal structure of the artificial zeolite itself is not changed, so the adsorption capacity of artificial zeolite material for phosphate cannot be improved. The hydrated metal oxide of lanthanum has a characteristic adsorption effect on phosphate anions. Lanthanum exists in the form of lanthanum oxide in zeolite materials, and the surface of the metal oxide is in an electron-deficient state, showing a Lewis acid, and combines with water molecules to form a hydrated oxide. The isoelectric point of hydrated lanthanum oxide is 10.4, and it is positively charged under acidic conditions. Therefore, it can produce electrostatic adsorption with phosphate ions to form a complex, thereby achieving the effect of removing phosphate from water.

[0027] According to the present invention, the lanthanum ion modified zeolite adsorbent can regain its adsorption capacity by desorbing the adsorbed phosphate ions in water and can be recycled.

[0028] The present invention also provides a lanthanum ion modified zeolite adsorbent prepared by the above preparation method.

[0029] The present invention also provides a water treatment method, comprising the following steps: using the lanthanum ion modified zeolite adsorbent prepared by the above preparation method to perform adsorption treatment on phosphorus-containing water.

[0030] In some embodiments provided by the present invention, the ratio of the lanthanum ion modified zeolite adsorbent to the phosphorus-containing water is preferably 0.2 g: (100-500) mL, more preferably 0.2 g: (100-400) mL, further preferably 0.2 g: (200-300) mL, and most preferably 0.2 g: 250 mL.

[0031] In some embodiments provided by the present invention, the mass concentration of phosphorus in the phosphorus-containing water is preferably 1-10 mg / L; optionally, the mass concentration of phosphorus in the phosphorus-containing water is 1 mg / L, 2 mg / L, 3 mg / L, 4 mg / L, 5 mg / L, 6 mg / L, 7 mg / L, 8 mg / L, 9 mg / L, 10 mg / L or a range between any two of the above values.

[0032] According to the present invention, the lanthanum ion-modified zeolite adsorbent after adsorption treatment is preferably shaken in water to obtain a regenerated lanthanum ion-modified zeolite adsorbent; the regenerated lanthanum ion-modified zeolite adsorbent is used for adsorption treatment of phosphorus-containing water bodies; the shaking treatment time is preferably 1 to 6 hours, more preferably 2 to 5 hours, and even more preferably 3 to 4 hours.

[0033] In order to further illustrate the present invention, a lanthanum ion modified zeolite adsorbent provided by the present invention, a preparation method thereof and application thereof are described in detail below in conjunction with examples.

[0034] The reagents used in the following examples are all commercially available; the artificial zeolite used in the examples and comparative examples is derived from the artificial zeolite produced by Shanghai MacLean.

[0035] Example 1

[0036] 1.1 The artificial zeolite was placed in a ball mill and crushed by dry ball milling (ball-to-material ratio 1:1), with stearic acid (added amount 0.1%) as a ball milling aid, at a ball milling speed of 8000 r / min, for 1 h, passed through a 150-mesh sieve, placed in a 2% sodium chloride aqueous solution with a solid-liquid ratio of 0.02 g / mL, stirred for 2 h, taken out and dried, and calcined at 500°C for 1 h to obtain modified zeolite.

[0037] 1.2 After cooling the modified zeolite in 1.1, put it into a 0.4% lanthanum chloride aqueous solution with a solid-liquid ratio of 1 g / 10 mL. After stirring for 2 h, calcine at 200°C for 1 h to obtain a lanthanum ion modified zeolite adsorbent.

[0038] 0.2 g of artificial zeolite, 0.2 g of modified zeolite obtained in 1.1, and 0.2 g of lanthanum ion modified zeolite adsorbent obtained in 1.2 were shaken in 250 mL of potassium dihydrogen phosphate solution with a phosphorus mass concentration of 5 mg / L for 3 h, and the concentration of phosphate was detected. The comparison of phosphorus adsorption performance of different materials was obtained as shown in the figure below: Figure 1 As shown. Figure 1 It can be seen that the adsorption of phosphate by the zeolite material after salt thermal modification is improved, but the increase is small. After loading the lanthanum element, the adsorption of phosphorus by the zeolite material is improved, which is a qualitative leap. Therefore, it is feasible to use the zeolite material after salt thermal modification and lanthanum ion loading as an adsorbent for phosphorus in water.

[0039] The lanthanum ion modified zeolite adsorbent after the above adsorption treatment was shaken in pure water for 3 h, filtered and dried to obtain a regenerated lanthanum ion modified zeolite adsorbent; 0.2 g of the regenerated lanthanum ion modified zeolite adsorbent was shaken in 250 mL of potassium dihydrogen phosphate solution with a phosphorus mass concentration of 5 mg / L for 3 h, the concentration of phosphate therein was detected, and the above steps were repeated to obtain the recycling results of the lanthanum ion modified zeolite adsorbent as shown in the figure. Figure 2 As shown. Figure 2 It can be seen that after oscillating in pure water, phosphate ions are desorbed from the zeolite material, allowing the zeolite material to regain its adsorption capacity, and its adsorption capacity tends to be stable after multiple desorptions. This proves that the modified zeolite material has strong recyclability as an adsorbent.

[0040] The commonly used adsorption isotherm models are the Langmuir model and the Freundlich model. The Langmuir model is a chemical adsorption model derived from a kinetic perspective, and is often used to describe simple monolayer adsorption; the Freundlich model is an empirical model and a physical adsorption model, and is often used to describe multi-molecular layer adsorption on heterogeneous surfaces.

[0041] Isotherm drawing: 250 mL of potassium dihydrogen phosphate water samples with phosphorus mass concentrations of 1, 2, 5, 10, 20, 50, and 100 mg / L were prepared respectively, and 0.2 g of the lanthanum ion-modified zeolite adsorbent obtained in Example 1 was added at 25°C for 24 h of oscillation adsorption to ensure that the adsorption reached equilibrium. The phosphorus content of different water samples after adsorption was measured respectively. The results were fitted according to two adsorption isotherm models, the Langmuir equation and the Freundlich equation.

[0042] Langmuir isotherm equation: , R 2 =0.9902 Freundlich isotherm equation: , R 2 =0.9878 Depend on Figure 3 It can be seen that at room temperature, the correlation coefficient R² of the Langmuir model is slightly higher than that of the Freundlich model, which means that the Langmuir model can more accurately describe the adsorption process of modified zeolite on phosphate than the Freundlich model. That is, the adsorption process of phosphate on lanthanum ion modified zeolite adsorbent is a simple monolayer adsorption, and there is no obvious force between the adsorbate molecules, which is a chemical adsorption process. High temperature activation and chemical treatment can change the structure of zeolite materials at the same time.

[0043] Example 2

[0044] 2.1 The artificial zeolite was placed in a ball mill and crushed by dry ball milling (ball-to-material ratio 1:1), with stearic acid (added amount 0.1%) as a ball milling aid, at a ball milling speed of 8000 r / min, for 1 h, passed through a 150-mesh sieve, placed in a 2% sodium chloride aqueous solution with a solid-liquid ratio of 1 g / 50 mL, stirred for 2 h, taken out and dried, and calcined at 500°C for 1 h to obtain modified zeolite.

[0045] 2.2 After cooling the modified zeolite in 2.1, put it into a 1% lanthanum chloride aqueous solution with a solid-liquid ratio of 1 g / 10 mL. After stirring for 1 h, calcination at 200°C for 1 h can obtain a lanthanum ion modified zeolite adsorbent.

[0046] Example 3

[0047] 3.1 The artificial zeolite was placed in a ball mill and crushed by dry ball milling (ball-to-material ratio 1:1), with stearic acid (added amount 0.1%) as a ball milling aid, at a ball milling speed of 8000 r / min, for 1 h, passed through a 150-mesh sieve, placed in a 2% sodium chloride aqueous solution with a solid-liquid ratio of 1 g / 50 mL, stirred for 2 h, taken out and dried, and calcined at 500°C for 1 h to obtain modified zeolite.

[0048] 3.2 After cooling the modified zeolite in 3.1, put it into a 1% lanthanum chloride aqueous solution with a solid-liquid ratio of 1 g / 10 mL. After stirring for 1 h, calcinate at 300°C for 1 h to obtain a lanthanum ion modified zeolite adsorbent.

[0049] Comparative Example 1 1.1 The artificial zeolite was placed in a ball mill and crushed by dry ball milling (ball-to-material ratio 1:1), stearic acid (added amount 0.1%) was used as a ball milling aid, the ball milling speed was 8000 r / min, the time was 1 h, passed through a 150-mesh sieve, placed in a 2% sodium chloride aqueous solution with a solid-liquid ratio of 0.02 g / mL, stirred for 2 h, then taken out and dried, and calcined at 200°C for 1 h to obtain modified zeolite.

[0050] 1.2 After cooling the modified zeolite in 1.1, put it into a 0.4% lanthanum chloride aqueous solution with a solid-liquid ratio of 1 g / 10 mL. After stirring for 2 h, calcine at 200°C for 1 h to obtain a lanthanum ion modified zeolite adsorbent.

[0051] 0.2 g of the lanthanum ion modified zeolite adsorbent obtained in Comparative Example 1 was shaken in 250 mL of potassium dihydrogen phosphate solution with a phosphorus mass concentration of 5 mg / L for 3 h, and the concentration of phosphate therein was detected; the lanthanum ion modified zeolite adsorbent after the above adsorption treatment was shaken in pure water for 3 h, filtered, and dried to obtain a regenerated lanthanum ion modified zeolite adsorbent; 0.2 g of the regenerated lanthanum ion modified zeolite adsorbent was shaken in 250 mL of potassium dihydrogen phosphate solution with a phosphorus mass concentration of 5 mg / L for 3 h, and the concentration of phosphate therein was detected to obtain the recycling result of the lanthanum ion modified zeolite adsorbent as shown in the figure. Figure 4 As shown. Figure 4 It can be seen that the adsorption capacity and desorption degree of the lanthanum ion modified zeolite adsorbent obtained in Comparative Example 1 are significantly reduced compared with the material calcined at high temperature.

[0052] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a lanthanum ion modified zeolite adsorbent, characterized in that: The following steps are involved: S1) mixing artificial zeolite particles with a sodium salt solution, stirring, filtering, drying, and calcining to obtain a precursor; the mesh size of the artificial zeolite particles is 100-300 meshes; the calcination temperature is 300° C.-500° C.; and the calcination time is 5 min-1 h; S2) mixing the precursor with a lanthanum salt solution, stirring, filtering, drying, and calcining to obtain a lanthanum ion-modified zeolite adsorbent; the calcination temperature is 200° C. to 400° C.; and the calcination time is 30 min to 2 h.

2. The preparation method according to claim 1, characterized in that: The sodium salt solution is selected from a sodium chloride solution; the mass concentration of the sodium salt solution is 0.5% to 2%; The lanthanum salt solution is selected from lanthanum chloride solution; The mass concentration of the lanthanum salt solution is 0.4% to 1%.

3. The preparation method according to claim 1, characterized in that: The artificial zeolite particles are prepared according to the following steps: The artificial zeolite is ball-milled and sieved to obtain artificial zeolite particles; the rotation speed of the ball mill is 200-11500 r / min; and the ball milling time is 1-8 h.

4. The preparation method according to claim 1, characterized in that: The ratio of the artificial zeolite particles to the sodium salt solution is 0.02-0.1 g:1 mL; The ratio of the precursor to the lanthanum salt solution is 0.05-0.1 g:1 mL.

5. The preparation method according to claim 1, characterized in that: The mixing and stirring time in step S1) is 2 to 3 hours; The mixing and stirring time in step S2) is 1 to 3 hours.

6. A lanthanum ion-modified zeolite adsorbent prepared by the preparation method according to any one of claims 1 to 5.

7. A method for water treatment, characterized in that: The following steps are involved: The lanthanum ion-modified zeolite adsorbent prepared by the preparation method according to any one of claims 1 to 5 is used to adsorb phosphorus-containing water.

8. The method according to claim 7, characterized in that The lanthanum ion modified zeolite adsorbent after adsorption treatment is shaken in water to obtain a regenerated lanthanum ion modified zeolite adsorbent; the regenerated lanthanum ion modified zeolite adsorbent is used for adsorption treatment of phosphorus-containing water bodies.

Citation Information

Patent Citations

  • Denitrification dephosphorization antibacterial composite water treatment material used for water reclamation

    CN101716489A

  • Lanthanum-iron modified zeolite phosphorus removal adsorbent and preparation method and application thereof

    CN109847691A

Cited By

  • Waste sulfuric acid treatment method and device

    CN121672821A